2023
DOI: 10.1038/s43705-023-00325-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbial composition and sharing in low-biomass human milk samples: a comparison of DNA isolation and sequencing techniques

Johanne E Spreckels,
Asier Fernández-Pato,
Marloes Kruk
et al.

Abstract: Human milk microbiome studies are currently hindered by low milk bacterial/human cell ratios and often rely on 16S rRNA gene sequencing, which limits downstream analyses. Here, we aimed to find a method to study milk bacteria and assess bacterial sharing between maternal and infant microbiota. We tested four DNA isolation methods, two bacterial enrichment methods and three sequencing methods on mock communities, milk samples and negative controls. Of the four DNA isolation kits, the DNeasy PowerSoil Pro (PS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…In the context of human milk and vertical transmission via breastfeeding, previous analyses of shared genera between HM and IS in the Dutch population [72] agree with the presence of Pauljensenia, but not with the presence of Streptococcus and Veillonella, which are shared in our work. Also, it has been shown that Bifidobacterium is bound to sIgA in HM [73], and the bacterium is transmitted by breastfeeding [74].…”
Section: Discussionsupporting
confidence: 77%
“…In the context of human milk and vertical transmission via breastfeeding, previous analyses of shared genera between HM and IS in the Dutch population [72] agree with the presence of Pauljensenia, but not with the presence of Streptococcus and Veillonella, which are shared in our work. Also, it has been shown that Bifidobacterium is bound to sIgA in HM [73], and the bacterium is transmitted by breastfeeding [74].…”
Section: Discussionsupporting
confidence: 77%
“…As the most comprehensive rrn database to date, and incorporating a GTDB-based version that includes numerous metagenome-assembled genomes (MAGs), this database should prove to be a valuable resource for the rrn sequencing community. Indeed, the preprint version of this database has already been used to study bacterial transmission in low-biomass human milk samples [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of classifier for phylogenetic analysis is significantly influenced by the type of long-read platform employed. The high accuracy of PacBio sequencing data makes it compatible with denoising or clustering pipelines, such as DADA2 [ 50 51 ] and vsearch [ 17 28 ], respectively. Meanwhile, the lower read quality from ONT demands specialised pipelines to account for its higher error rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there is no evidence of harmful bacteria being selected in carbonated raw milk during refrigeration. However, next‐generation amplicon sequencing offers advantages such as greater sampling depth, less manual processing and more representative and reproducible results (Catozzi et al ., 2020; Spreckels et al ., 2023). Therefore, the aim of this current study is to analyse the bacterial composition of carbonated raw milk during cold storage using Illumina sequencing of the 16S rRNA gene amplicon (García‐González et al ., 2022; Baptista & Domingues, 2023; Busetta et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%